The frequency and relationship of flowering plants on the distribution pattern of Ophiocordyceps sinensis (Yarchagunbu) in the highlands of Dolpa district, Nepal - Devkota, S (Banko Janakari, 2009)
Ophiocordyceps sinensis (Berk.) G.H. Sung, J.M. Sung, Hywell-Jones & Spatafora is a highly valuable medicinal fungus. Biologically it is an entomopathogenic, entomophagous or entomophilous fungus. In order to investigate different floral associations with O. sinensis, and to know different threats to pasture biodiversity, research was conducted in three pastures of Raha and Majphal Village Development Committees of Dolpa district. The study revealed that Juncus thomsonii and Bistorta macrophylla were the principal plant associates with O. sinensis as they dominated the alpine pasture vegetation. This research also highlighted the need for some proactive solutions along with conservation awareness program as important management initiatives to ensure ecological balance of O. sinensis. Key words: Alpine zone, flora, Ophiocordyceps sinensis, pasture management, Yarsagumba doi: 10.3126/banko.v19i1.2180 Banko Janakari, Vol. 19, No. 1, 29-36